STIFFNESS AND STRENTH ANALYSIS OF A LUG JOINT STRUCTURE - WANG CongWei; FANG ZePing; NIU Fei; TIAN WeiFeng; LIANG ZuDian (Jixie qiangdu)
Lug joint is a kind of structure widely used in missile empennages connection. Aiming at the problem of the lug joints in a static experiment,we built the equal simplified FEA model,and systematically analyzed the influence of bolts distribution,stiffness matching of connected parts,bolt fit clearance and bolt preload on stiffness and strength of the joints.Finally,based on the analysis and manufacturability,the original structure got improved and validated by FEA simulation.